Floodplains on the prairie: an ecological schoolyard design - Weatherholt, Laura (Kansas State University, 2012)
Man has been learning in the outdoors since the beginning of humankind. Modern times have reduced the amount of time people spend learning and exploring outside. This causes humans to be disconnected from the natural environment. By making schoolyards more environmentally focused, conducive to outdoor education and play, formal education can return to the original classroom–nature– and inspire people to reconnect with their environment. Much literature supports the ideas of aligning the efforts of play and education, environmental interpretation and education, and outdoor education with formal education; by incorporating all of these elements in a schoolyard, the potential for enriched learning is greatly increased. This project explores nature interpretation strategies used by public botanic gardens and translates these strategies to an ecological schoolyard. At Northview Elementary School in Manhattan, Kansas, the students face a simple, sterile play-yard with flooding limiting site use after storm events. The design for Northview Elementary will integrate stormwater features with school needs into a new ecological master plan for campus. Interpreting this landscape using the strategies adapted from botanical gardens for educational approaches, methods, and interpretive displays, provides the school and community a resource to enhance their lives, education, and the environment.
Keywords: Landscapes of learning; Ecological schoolyard; Natural learning; Outdoor education; Play; Environmental education (0442); Landscape Architecture (0390)